Students’ Perception and Satisfaction with Online Medical Education During the COVID-19 Pandemic - Rashid, Tahmina Joy; Ahmed, Tarafder Shahniam; Giasuddin, Rubayat Sheik; Rowshan, Mahfuza Majeda; Any, Omma Hafsa; Jahid, A B M Masud (British Journal of Healthcare and Medical Research, 2024)
Background: The COVID-19 pandemic caused countries worldwide to implement emergency lockdown strategies and caused disruption of medical education. The pandemic motivated the development of medical educational strategies. Objectives: The aim was to determine medical students’ perception and satisfaction with online medical education during the pandemic. Materials and Methods: A cross sectional descriptive analytical study was conducted with structured self-administered questionnaire on the different domains of online education on 120 medical students. Data was analyzed by SPSS software. Results: Among the 120 students, 72 were females and 48 males. 70% had no prior experience with online education but 30% did. More than 79% agreed online training was essential. About 61% disagreed that online classes facilitated effective faculty-student interactions, and 60% were not satisfied with quality of online teaching learning sessions. About 84.2% agreed they had appropriate online devices and 56% had stable internet. About 70% were satisfied with teacher’s knowledge and 70% felt they could ask questions and 43% were satisfied with teaching mode. About 45% felt they had feedback from teachers after assessments and 48.3% were satisfied with online exam performance. Conclusion: The findings have shown that students’ perceptions and satisfaction level serve as important indicators of online medical education. Continuous training and research in this field are essential for both faculty and students to enhance online teaching-learning skills.